The implementation of the Guaranteed Minimum Income in times of COVID19: implications for Social Services in Spain - Muriel-Saiz, Mercedes; Gutiérrez-Sastre, Marta; Páez-Izquierdo, Virginia (Áreas. Revista Internacional de Ciencias Sociales, 2023)
Minimum income policies are one of the social measures that have the greatest impact on social protection systems. After a year and a half since the implementation of the Guaranteed Minimum Income (IMV in Spanish) in Spain, this article aims at analyzing the perception of social workers on the effects of this new economic benefit on public Social Services. For this purpose, a qualitative methodology is followed, through a total number of six rounds of interviews in fifty-two social services centers located in different territories of the Spanish context. A total of 364 telephone interviews of 52 social service centers were conducted between July 20200 and September 2021. The results of this research point out to the unfulfilled expectations generated, the subordination of the social services to other institutional spheres, the bureaucratization of tasks and oversight in the social intervention processes, as well as the lack of recognition of social services’ professionals regarding the management of this provision.